Electrodeposited molybdenum selenide sheets on nickel foam as a binder-free electrode for supercapacitor application. (1st March 2018) - Mariappan, Vimal Kumar; Krishnamoorthy, Karthikeyan; Pazhamalai, Parthiban; Sahoo, Surjit; Kim, Sang-Jae
Abstract: Two-dimensional nanostructured metal chalcogenides have significant consideration as electrode materials for energy storage application owing to their fascinating properties. In this work, we have grown two-dimensional MoSe2 sheets directly on the surface of nickel foam via facile one-step electrochemical deposition method and examined their use as a binder-free electrode for supercapacitor. The physicochemical characterizations such as X-ray diffraction, field emission scanning electron microscope, X-ray photoelectron spectrum, and Raman analysis confirmed the formation of MoSe2 sheets on Ni foam. The effect of deposition time (5 and 10 min) on the electrochemical properties of the MoSe2 sheets are examined in detail using cyclic voltammetry, galvanostatic charge-discharge, and electrochemical impedance spectroscopic analyses, respectively. The cyclic voltammetry profiles confirmed that the charge-storage mechanism in MoSe2 sheets is due to the ion intercalation/de-intercalation kinetics. A high specific capacity of 548 mAh g −1 was obtained for the MoSe2 /Ni electrode from CV profile measured using a scan rate of 5 mV s −1 . The MoSe2 /Ni electrode delivered a specific capacity of 325.92 mAh g −1 from charge-discharge analysis obtained at constant discharge current density of 4 mA cm −2 with good cyclic stability. The capacitive properties and the mechanism of charge-storage in the MoSe2 /Ni electrode deposited at different time intervals were examined by the electrochemical impedance spectroscopy using Nyquist and Bode phase angle plot. The experimental results ensure that the MoSe2 /Ni electrode might be used as the high-performance electrode for the next-generation energy storage devices. Highlights: A facile electrochemical deposition of MoSe2 sheets on Ni foam was demonstrated. Field emission scanning electroscope confirms the growth of MoSe2 sheet on Ni foam. Raman spectrum revealed the formation of few layered MoSe2 sheets on Ni foam. The binder free MoSe2 electrode delivered a high specific capacity of 548 mAh g −1 . The MoSe2 /Ni electrode shows excellent cyclic stability over 1000 cycles.